The Emergence Of Homonyms In The Semantic Method - M. Abdurakhmanova (Research Parks Publishers, 2022)
The article deals with the formation of homonyms semantically. Analysis of homonyms, the role of thinking, linguistic consciousness, perception in the understanding of homonyms. The order of meaning comprehension on the basis of homonyms is analyzed. On the basis of examples, the method of forming homonyms in the semantic method is analyzed